A risk based assessment approach for chemical mixtures from wastewater treatment plant effluents. (June 2022) - Finckh, Saskia; Beckers, Liza-Marie; Busch, Wibke; Carmona, Eric; Dulio, Valeria; Kramer, Lena; Krauss, Martin; Posthuma, Leo; Schulze, Tobias; Slootweg, Jaap; Von der Ohe, Peter C.; Brack, Werner
Graphical abstract: Highlights: 366 chemicals detected in 56 European WWTP effluents at <1 ng/L to >100 µg/L. Three different risk metrics (RQ, HU, TU) provided complementary information. 293 mixture components of concern exceeded the risk threshold. 32 consensus mixture risk contributors of high concern identified. Activated carbon and ozonation treatments reduced toxic risks below thresholds. Abstract: In this study, 56 effluent samples from 52 European wastewater treatment plants (WWTPs) were investigated for the occurrence of 499 emerging chemicals (ECs) and their associated potential risks to the environment. The two main objectives were (i) to extend our knowledge on chemicals occurring in treated wastewater, and (ii) to identify and prioritize compounds of concern based on three different risk assessment approaches for the identification of consensus mixture risk drivers of concern. Approaches include (i) PNEC and EQS-based regulatory risk quotients (RQs), (ii) species sensitivity distribution (SSD)-based hazard units (HUs) and (iii) toxic units (TUs) for three biological quality elements (BQEs) algae, crustacean, and fish. For this purpose, solid-phase extracts were analysed with wide-scope chemical target screening via liquid chromatography high-resolution mass spectrometry (LC-HRMS), resulting in 366 detected compounds, with concentrations ranging from < 1 ng/L to > 100 µg/L. The detected chemicals were categorized with respect to critical information relevant for risk assessment and management prioritization including: (1) frequency of occurrence, (2) measured concentrations, (3) use groups, (4) persistence & bioaccumulation, and (5) modes of action. A comprehensive assessment using RQ, HU and TU indicated exceedance of risk thresholds for the majority of effluents with RQ being the most sensitive metric. In total, 299 out of the 366 compounds were identified as mixture risk contributors in one of the approaches, while 32 chemicals were established as consensus mixture risk contributors of high concern, including a high percentage (66%) of pesticides and biocides. For samples which have passed an advanced treatment using ozonation or activated carbon (AC), consistently much lower risks were estimated.